Improvement of pervaporation PVA membranes by the controlled incorporation of fullerenol nanoparticles. (15th April 2016) - Penkova, Anastasia V.; Acquah, Steve F.A.; Dmitrenko, Maria E.; Sokolova, Maria P.; Mikhailova, Mariya Е.; Polyakov, Evgeny S.; Ermakov, Sergey S.; Markelov, Denis A.; Roizard, Denis
Abstract: This work focuses on the incorporation of fullerenol nanoparticles to get PVA-fullerenol mixed matrix membranes for alcohol dehydration by pervaporation. Cross-linked hybrid membranes based on composites of polyvinyl alcohol (PVA) and low-hydroxylated fullerenol C60 (OH)12 have been prepared by two different procedures. To improve the dispersion of the functionalized fullerene in the PVA network, the hydrodynamic properties of PVA, fullerenol and PVA/fullerenol composites in dilute solutions were studied by viscometry and dynamic light scattering. It was shown that the aggregate sizes increased with the increase of fullerenol content in the PVA/fullerenol composite solutions. The effect of low-hydroxylated fullerenol on the structure and morphology of PVA membranes was investigated by small-angle X-ray scattering and atomic force microscopy. It was observed that the incorporation of 5 wt.% fullerenol and cross-linking with maleic acid led to a more uniform distribution of the amorphous PVA phase. As a result, membrane transport characteristics were improved for the dehydration of n -butanol–water mixtures by pervaporation. The PVA membranes containing 35 wt.% maleic acid and 5 wt.% fullerenol exhibited the best transport properties. Graphical abstract: Highlights: Membranes based on polyvinyl alcohol and fullerenol C60 (OH)12 have been prepared. Two different cross-linking approaches of PVA membrane were performed. The relationship between casting solutions and membrane properties was studied. PVA composites membranes were studied for the pervaporation of n -butanol–water mixture. All membranes were essentially selective with respect to water.